Hydrochemical characteristics and metallic quality in fish in the Loukkos river estuary of Morocco - El Morhit, M.; Fekhaoui, M.; El Morhit, A.; Elie, Pierre; Yahyaoui, A. (HAL CCSD, 2013)
The region of Larache endures a big problem of pollution of the surface waters. This pollution takes various origins, domestic, agricultural and industrial. The study of the physicochemical characteristics (Water temperature, pH, Salinity, DO, Conductivity, SM, TOC, NO3, COD and BOD) of the effluents exits of the industrial units of the Loukkos river estuary shows, that these units are responsible of important organic discharges and heavy metals. Indeed, the wastewaters used to drain rice fields are at the origin of important organic discharges which drag strong concentrations in SM and NO3, also most effluents present a strong salinity (conductivity) and TOC concentration. This high level of pollutants concentration can be a main cause of poisoning for the receiving environment. They especially conjugate themselves by the waters qualities deteriorate of the Loukkos river estuary downstream. The assessment of the metals concentration studied (Fe, Zn, Cu, Cr, Pb and Cd) in the sediments and the superficial waters revealed the presence of a wide metallic contamination, mainly in the river’s downstream. Fish species (Liza ramada, Barbus callensis and Anguilla anguilla) were collected in the Loukkos river estuary, whereas (Pagellus acarne, Sardina pilchardus and Diplodus vulgaris) were collected in the northern Atlantic coast of Morocco in 2006 and 2007. Concentrations of selected metals were measured using an atomic absorption spectrophotometer (AAS). Significant correlations (P<0.05) between Cu–Pb were observed in sediments, Fe–Pb, Cr–Pb and Cr–Fe in water and Zn–Fe in fish. The metal levels found in the muscles of fish species were below the legal limits for human consumption, but can induce sever dysfunctioning for the eel.